Photodegradation of natural dye / Muhammad Uwais Addin Muhamad Najibmudin - Muhamad Najibmudin, Muhammad Uwais Addin (2023)
Decades have been spent utilising non-renewable energy especially in power generation. The transition of this energy source to renewable energy was begin by many researchers. Dye-sensitized solar cell is an excellent way to generate electricity. The research has been done to analyze the effect of metal oxide on natural dye conductivity, the effect of sunlight toward the dye colour and conductivity and to investigate the outcome of metal oxide exposure to sunlight. The photodegradation was done by adding calcium oxide into the dye solution and time exposed it to the sunlight as the parameter. The result of this study demonstrates the correlation of conductivity, dye colour and CaO frequency to the sunlight. Dye conductivity and colour intensity was decreased as the molecules of dye was reduced by the sunlight. The frequency of CaO also has been affected by the sunlight. The study found that exposure to sunlight decreased the dye's colour intensity and conductivity value. FTIR showed that the CaO had a similar peak to the dye. A dye-sensitized solar cell is an environmentally friendly alternative to current electricity generators.